A mini review of the state-of-the-art development in oil recovery under the influence of geometries in nanoflood - Mudasar, Zafar; Hamzah, Sakidin; Abida, Hussain; Sheremet, Mikhail A.; Iskandar, Dzulkarnain; Rizwan, Safdar; Roslindar, Nazar; Al-Yaari, Abdullah; Mohd Zuki, Salleh; Daabo, Ahmed; Khan, Iliyas Karim (Semarak Ilmu Publishing, 2024)
The global demand for oil and petroleum products is experiencing a significant increase, while the number of newlydiscovered oil reservoirs is relatively low. This emphasises the critical need for innovative techniques to enhance the rate of oil recovery in order to meet global demand. The implementation of nanotechnology in enhanced oil recovery (EOR) yields numerous advantages, including cost savings in production and improved oil recovery. Additionally, it is critical to investigate the geometrical behaviour of the reservoir, as this information is vital for determining the maximum oil recovery rate. This review highlights the significance of nanotechnology through the utilisation of various geometries to determine the rate of hydrocarbon recovery. Furthermore, this paper also addresses the obstacles associated with achieving maximum oil recovery and provides suggestions for future research in this field. The review concludes with its key finding, which indicates that an examination of reservoir geometry utilising nanofluid in the presence of electromagnetic waves can significantly improve the rate of hydrocarbon recovery.